PROTOTYPE DESIGN ROBOT MONITORING REMOTE CONTROL BASED ON FIRST-PERSON VIEW - Jhoni Hidayat; Dwiyanto Dwiyanto; Usman Usman (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Technological advances are not only used for the industrial world but have led to all fields both education, military, and household. One of the technological advances in the application of robots that are used to reduce the use of human power. Therefore, the design of a remote control monitoring robot prototype that is used to replace the human role in monitoring or monitoring certain objects or environments that are difficult to reach by humans to go directly to the intended object. This robot is designed by applying the FPV (First-Person View) system which is controlled remotely using the nRF24L01 and MPU6050 and uses a servo to move the camera. Based on the results of testing the Robot Prototype in this study as a whole, the prototype robot is obtained well and the Robot Prototype can replace the role of humans in monitoring objects remotely. Keywords: Arduino; FPV; Monitoring; nRF24L01; MPU6050; Robot.  Abstrak: Kemajuan teknologi tidak hanya digunakan untuk dunia industri saja melainkan sudah mengarah ke segala bidang baik dunia pendidikan, militer dan dalam rumah tangga. Salah satu kemajuan teknologi adalah penerapan robot yang digunakan untuk mengurangi penggunaan tenaga manusia. Maka dari itu dilakukan perancangan prototype robot pemantau kendali jarak jauh yang digunakan untuk menggantikan peran manusia dalam pengawasan atau pemantauan objek ataupun lingkungan tertentu yang sulit dijangkau oleh manusia untuk terjun langsung ke objek yang dituju. Robot ini dirancang dengan menerapkan sistem FPV (Fisrt-Person View) yang dikendalikan dari jarak jauh menggunakan nRF24L01 dan MPU6050, serta menggunakan servo untuk menggerakan kamera. Berdasarkan hasil pengujian prototype robot pada penelitian ini secara keseluruhan didapatkan prototype robot dengan baik dan prototype robot dapat menggantikan peran manusia dalam pemantauan objek dari jarak jauh. Kata kunci: Arduino; FPV; Monitoring; nRF24L01; MPU6050; Robot.